Characterization of the oncornavirus particles in the plasma of guinea pigs with L2C leukemia. - Michalides, R (1976)
The inoculation of L2C guinea pig leukemia cells into strain 2 guinea pigs results in the death of the animals within 12 to 15 days. Death is preceded by the simultaneous appearance in the plasma of (i) elevated leukocyte levels, (ii) extracellular virus particles, and (iii) a particle-associated RNA-directed DNA polymerase. This enzyme activity has a cation preference identical to that of the type B bromodeoxyuridine-induced guinea pig virus, i.e., an Mg2+ optimum at 20 mM and no activity using Mn2+. Competitive molecular hybridization studies also revealed that the plasma of leukemic guinea pigs contained approximately 2 X 10(9) genome equivalents per ml of an RNA that is homologous to the RNA of the bromodeoxyuridine-induced guinea pig virus. Morphological observations indicate that most, but not all, of the extracellular particles observed in leukemia plasma are derived from the intracisternal particles seen in the L2C tumor cells. The possibilities that either two viral populations are present or that the in vivo morphogenesis of the type B bromodexoyuridine-inducible guinea pig virus is markedly different from its in vitro morphogenesis are discussed.